Heart rate variability and autonomic activity in young short-track athletes at the age of 14 - Brook, T. M.; Litvin, F. B. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the features of heart rate regulation and autonomic regulation for an orthostatic test in 14-year-old short-track athletes in the pre-competition training period.